Exploring reasons of variation in target achievement in sanitary latrine construction under school sanitation programme of BRAC WASH - Arif, Tahmid; Ahmed, Shamim (BRAC Research and Evaluation Division (RED), 2019)
Since 2007 BRAC's Water, Sanitation and Hygiene (WASH) programme has been promoting construction of sanitary latrines with water source and waste management provision at the girls' secondary educational institutes in 150 sub·districts across Bangladesh. In all cases BRAC offered partial financial support for constructing sanitary latrines and rest of the cost was managed by the school authority. Three educational institutes from each union in a sub·district were considered for this intervention. Each educational institute received Tk. 35,000 from BRAC for procuring construction materials. However, it was observed that target achievement in constructing sanitary latrine was not equal in all the regions. For instance, in the south target achievement was lower compared to the north. Although, it was assumed that in the south achievement would be higher compared to the north as socioeconomic status of the south is better compared to the north. This study explored the reasons of different levels of target achievement in constructing sanitary latrine for girls' in those two regions. A qualitative study was done in Bogra, Thakurgaon, Khulna and Jessore districts. The first two districts were selected from the north and the rest two districts from the south. Each sub·district represented one district. From each sub·district five unions were selected for this study. Data were collected through focus group discussions, in-depth interviews and observations from WASH staff, school teachers, school management committee (SMC) members and guardians. Findings show that financial support of BRAC played a vital role in attracting majority of the institutions to construct the sanitary latrine. However, for some of the institutions particularly for those in the south, the amount of money allocated by BRAC was not attractive. It also shows that unanticipated price hike of construction materials, natural disasters such as cyclone and flood, political affiliatjon, unwillingness of some of the SMC members and school authorities, negotiation-related issues, school selection criteria and misconception about BRAC were some other major constraints against achieving the target in the south. Whereas in the north, necessity and design ofthe latrine, donation from the community people, self interest of teachers; SMC members and guardians, role of village WASH committee, role of female teachers, reputation of BRAC and support from the union parishad chairmen helped in achieving the target.